PENGARUH PRICE, PEOPLE, PROCESS, DAN PHYSICAL EVIDENCE TERHADAP BRAND IMAGE - Kris Wibisono (Universitas Mercu Buana, 2014)
Abstract. Inwinning the competition, companiesmust have amarketing strategy for their products, one of which was adecision in which branding is important in building the image of a product. The purpose of this study was to determine the effect of simultane ousand partial, as well asthe most dominant influence on the price,people, process, and physical evidence to the brand image Mercu Buana Universityin 2013. Tomeasure these variables, used questionnaires sub mitted to student of Mercu Buana University. Population and samples taken areas many as 100 respondents. Then test Heteroskidastity, Multicollinearitytest, F test, t test, coefficientof determination, Multiple Linear Regression. Based this study obtained results that the price has positive and significant, positive effect and people are not significant, positive impact and significant process, physical evidence and no significant positive effect on brand equity.Keywords: price, people, process, physical evidence, brand image.